Gerakan Mahasiswa: Studi Tentang Aliansi Cipayung Kota Bandung Dalam Aksi Bandung Darurat Korupsi - Rizkiah Rizkiah; R. Widya Setiabudi Sumadinata; Yusa Djuyandi (Mahesa Research Center, 2021)
This study uses qualitative data interview techniques Cipayung Alliance Bandung City and is equipped with a literature review. The results showed that the movement carried out by the Bandung City Cipayung Alliance in the Bandung Corruption Emergency Action was a moral movement. This movement is a part that must be done because the idea of every student organization that is part of the Bandung City Cipayung Alliance is to activate the weak. Corruption is a crime that results in losses for the government of Bandung City. The pattern of movement carried out in Bandung Emergency Corruption is through discussion, then carrying out street activities and making the media an organizational tool as well as a tool for campaigns related to issues. Ihtiar examining the internal provides comprehensive insight and knowledge. The problem is, to see and believe that this movement is a movement that deserves to be carried out and fought for.